Kitten Chaos - Faruqi, Saadia (Faruqi, Saadia. Must love pets, 2022)
"Must Love Pets has a new job: pet sitting three adorable kittens. What Imaan, London, and Olivia don't expect is all the trouble these tiny creatures can get into, from climbing the curtains, to crawling on kitchen counters, and spilling baking supplies everywhere. To get out of the house--and out of Mama's hair--the girls take the kittens to a local farmers' market. There, they meet the world's cutest goat, and the kittens have a ball. At the end of a busy day as fabulous pet sitters, the girls are relaxing back at Imaan's house when they realize two things: The goat has followed them home, and the kittens are nowhere to be found. They'll have to solve two animal emergencies before anyone finds out."--